Penerapan Metode Pendrilan Dalam Upaya Meningkatkan Hasil Belajar Praktikum Akuntansi Perusahaan Jasa, Dagang Dan Manufaktur Pada Siswa Kelas XII AKL 3 SMKN 1 Dumai Tahun 2022 - Herawaty, Alfiah (Benefit: Journal of Bussiness, Economics, and Finance, 2023)
This study aims to improve the learning outcomes of Service, Trade and Manufacturing Companies Accounting Practicum with the drill learning method. The formulation of the problem that has been compiled by the researcher is: "Is using the drill method able to improve learning outcomes in the Accounting Practicum for Service, Trade and Manufacturing Companies for Class XII AKL 3 students at SMK Negeri 1 Dumai. This research is carried out in the form of class action research in 2022, in odd semester. The subjects of this study were 35 students of Class XII AKL 3. Data analysis used descriptive qualitative analysis. Research determines the aspects observed in each indicator of learning outcomes. The results of research on the chapters that have been discussed can be concluded that using the drill method can improve student learning outcomes of Class XII AKL 3 SMK Negeri 1 Dumai, subject of Service Company Accounting , Trade and Manufacturing on the subject of Practicum Accounting for Services, Trade and Manufacturing Companies. After taking action in the first cycle, students' cognitive learning outcomes increased student learning outcomes. the basic score with an average of 70.82 increased in the first daily test to 86.64 with a completeness level of 94.29%. In Daily Deuteronomy II it increased to 88.9 with a 100% completeness level. Then obtained an increase in learning outcomes from repetition I and repetition II which is very significant